On vertical relations and the timing of technology adoption - Maria Alipranti; Chrysovalantou Milliou; Emmanuel Petrakis (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
We study the timing of new technology adoption in markets with input outsourcing, and thus with vertical relations. We find that technology adoption can take place earlier when firms engage in input outsourcing than when they produce the input in-house. Hence, the presence of vertical relations can accelerate the adoption of a new technology. We also find that particular features of a vertically related market, such as the bargaining power distribution and the contract type through which trading is conducted, can crucially affect the speed of technology adoption.
Keywords: L13; O31; L22; L41; 330; technology adoption; vertical relations; outsourcing; two-part tariffs; wholesale price contracts; bargaining